A MAKNA LEKSIKAL DAN KULTURAL DALAM TUTURAN MAKKOBAR BORU PADA ACARA PERNIKAHAN MASYARAKAT BATAK MANDAILING DI KABUPATEN PADANG LAWAS - Siregar, Putri; Radhiah; Wulanda; Larasati, Dewi (Journal of Practice Learning and Educational Development, 2026)
This research aims to analyze the lexical and cultural meanings contained in the oral tradition of makkobar boru during wedding ceremonies of the Mandailing Batak community in Padang Lawas Regency. The object of the research is the makkobar boru speech. This research uses a descriptive qualitative approach with content analysis techniques. Data were collected thru direct observation, interviews with traditional leaders and the families of the bride and groom, as well as documentation of the wedding ceremonies taking place in three villages in the Barumun Tengah District, namely Pasar Binanga Village, Unterudang, and Siolip. Then, data triangulation was conducted using Norman K. Denkin's theory. The research results show that the makkobar boru speech contains vocabulary typical of Mandailing that reflects kinship, moral, and spiritual values. Culturally, this speech represents the worldview of a society that upholds customs, gender roles, and harmony within the dalihan na tolu structure. This tradition serves as a medium for customary communication and a means of passing on cultural values to the younger generation.